The effect of fuel prices on agri-food sector output in Ghana - Ramatu Ussif; Jamal Mohammed; Ussif Abdul-Aziz Sirin (Cogent Economics & Finance, 2024)
This paper applied the Cobb-Douglas production function to look into the impact of global crude oil prices on agricultural output in Ghana. Annual time-series secondary data spanning from 1980 to 2020 were utilized, sourced from the World Development Indicators and the US Energy Information Administration. The variables employed included agriculture value added per gross domestic product (GDP), international Brent crude oil prices, agricultural employment as a percentage of total employment, Tractors and agricultural equipment, as well as the proportion of land used for agriculture. To investigate the short- and long-term correlations between these variables, the Autoregressive Distributed Lag (ARDL) cointegration technique was employed. A unit root test was performed to evaluate the stationarity of the variables before ARDL analysis. The EViews Statistical/Econometric package facilitated the analysis. The findings from the ARDL cointegration estimates revealed a negative correlation between international crude oil prices and agriculture value added per GDP. According to the model, all variables exhibited cointegration over both the short and long term. Control variables, including agricultural employment as a percentage of total employment and agriculture machinery and tractors, showed a positive correlation with agriculture value added per GDP. However, agricultural land was found to be insignificant in influencing agricultural output. The research evinced a negative effect of crude oil prices on agricultural output in Ghana, hence rising fuel cost could trigger food insecurity and threatens livelihoods, highlighting the need for policy interventions that stabilize energy costs and support sustainable agricultural practices.
Keywords: C53; O1; Q1; Q4; 330; agri-food sector; Autoregressive Distributed Lag (ARDL); Cobb-Douglas production function; Fuel prices; Ghana